The Influence of Digital Marketing, Branding, Electronic Word of Mouth, and the Reputation of Islamic-Based Educational Institutions on the Decision to Join Islamic Schools - Khadafie, Muammar; Oktapiani, Serli (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to analyze the influence of digital marketing, branding, electronic word-of-mouth (e-WOM), and reputation on the decision to enroll in Islamic schools. Methods: The research employs multiple linear regression analysis to test the proposed hypotheses. Results: The findings indicate that digital marketing has a positive but statistically insignificant effect (β ≈ 0.092, p = 0.269) on enrollment decisions. In contrast, branding (β ≈ 0.263, p < 0.001), e-WOM (β ≈ 0.297, p = 0.012), and reputation (β ≈ 0.412, p < 0.001) exert significant positive influences, with reputation as the most dominant factor. The overall regression model is statistically significant (F = 120.1, p < 0.001), with an R² of 0.624, explaining 62.4% of the variability in enrollment decisions. Islamic schools should prioritize strengthening branding, leveraging e-WOM, and maintaining robust reputations to boost enrollment rates, while optimizing digital marketing through integration with other strategies for greater impact. Novelty: This study offers actionable insights for Islamic educational institutions to enhance their competitive edge in the sector, particularly by identifying key drivers beyond digital marketing—such as branding, e-WOM, and reputation that significantly shape enrollment decisions.